2021
DOI: 10.1002/mnfr.202100170
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Berry Anthocyanins on Vascular Function

Abstract: Cardiovascular disease (CVD), such as hypertension and atherosclerosis, is the leading cause of global death. Endothelial dysfunction (ED) is a strong predictor for most CVD making it a therapeutic target for both drug and nutrition interventions. It has been previously shown that polyphenols from wine and grape extracts possess vasodilator activities, due to the increased expression and phosphorylation of the endothelial nitric oxide synthase (eNOS), and consequent vasodilator nitric oxide (NO) production. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 136 publications
(129 reference statements)
0
22
0
Order By: Relevance
“…Conflicting results were found in studies with postmenopausal women, or adults with prehypertension or hypertension, in which a daily intake of 150–400 mg nitrate over periods ranging from 10 days to 12 weeks increased NO (measured by nitrate in urine or plasma) but did not reduce SBP or DBP [ 47 , 48 , 49 , 50 ]. The consumption of fruits and vegetables, as a source of polyphenols, could induce NO production by increasing endothelial nitric oxide synthase (eNOS) activity and reducing oxidative stress and inflammation [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results were found in studies with postmenopausal women, or adults with prehypertension or hypertension, in which a daily intake of 150–400 mg nitrate over periods ranging from 10 days to 12 weeks increased NO (measured by nitrate in urine or plasma) but did not reduce SBP or DBP [ 47 , 48 , 49 , 50 ]. The consumption of fruits and vegetables, as a source of polyphenols, could induce NO production by increasing endothelial nitric oxide synthase (eNOS) activity and reducing oxidative stress and inflammation [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some researchers suggest that polyphenols could improve the metabolism of NO through the L-arginine-NOS pathway, enhancing the activity of eNOS, which is activated via Pi3K/Akt [ 60 , 62 , 63 , 64 ]. In addition, reactive oxygen species can be inhibited by polyphenols, thereby reducing oxidative stress and the upregulation of inflammatory markers within the endothelium and upregulating NO synthesis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin 3-glucoside decreased inflammation, suppressed apoptosis, lowered blood lipid concentrations and improved artery wall structure and function in rabbits fed a high-fat diet [ 202 ]. Berry anthocyanins may protect the vasculature in cardiometabolic disease by inducing NO production and decreasing inflammation and oxidative stress [ 203 ] as well as changes in the gut microbiota [ 204 ]. Further, Queen Garnet plum juice containing approximately 250 mg cyanidin 3-glucoside reduced the postprandial effects of a high-fat high-energy meal on vascular endothelial function and inflammatory responses in older humans [ 205 ].…”
Section: Therapeutic Actions Of Anthocyanins In Chronic Diseasesmentioning
confidence: 99%
“…Berries are rich in polyphenols, flavonoids, vitamins, fiber, and minerals [174]. A trial sequence analysis reported berries as a nutraceutical or functional food to prevent and control cardiovascular disease [175].…”
Section: In Vitro and In Vivo Studies Of Food 71 Berriesmentioning
confidence: 99%